P05.13 Long term clinical outcomes with helical tomotherapy based image guided intensity modulated radiotherapy for benign and low grade brain tumours. (19th September 2018) - Maitre, M P; Gupta, T; Krishnatry, R; Goda, J S; Epari, S; Chinnaswamy, G; Moiyadi, A; Jalali, R
Abstract: Background: To report long term clinical outcomes of patients with residual, recurrent or progressive benign and low grade brain tumours, treated with helical tomotherapy (HT) based image-guided intensity-modulated radiation therapy (IG-IMRT). Material and Methods: Patients with residual, recurrent, or progressive benign/low grade intracranial tumours, treated with HT based IG-IMRT at our institution from 2008–2017 were included in this study. All patients underwent comprehensive baseline neurological assessment before RT. RT planning CT scan of every patient was co-registered with magnetic resonance imaging (MRI) for target volume delineation. HT based IMRT planning was used to achieve highly conformal target volume coverage and minimized dose to critical normal structures in close proximity. Daily setup verification was done for every patient using on-board megavoltage imaging. Patients were followed up clinicoradiologically with serial MRI scans. Tumour control was defined as lack of evidence of tumour progression on serial imaging. Progression was defined as either imaging-defined or clinically observed sustained neurologic worsening. Results: 160 patients (76 males, 84 females) were eligible for analysis, with median age at RT being 37 years (range 5–72 years). Most common diagnoses were meningioma (n=70, 44%), pituitary adenoma (n=27, 17%), craniopharyngioma (n=17, 11%), schwannoma (n = 15, 9%) and optic pathyway glioma (n=13, 8%). Tumour location was sellar/suprasellar in 41%, cerebral hemispheric in 30%, and skull base in 22% patients. Indications of RT included postoperative RT for residual disease (51%), RT for recurrent/progressive disease (28%) and radical RT for inoperable disease (20%). 93% patients had undergone some form of surgical excision before RT. All patients had good Karnofsky performance status (median KPS = 90). 43 % patients had pre-existing neurological deficits before starting RT, including tumour-induced as well as post-surgical deficits. Median planned radiotherapy dose was 54 Gy in 30 fractions. Post RT acute toxicities were mild and self-limiting, with no reported grade III/IV toxicity. 92% patients showed improved or stable neurological deficits following RT. On follow-up imaging, 88% lesions were stable or decreased in extent compared to pre-RT scan, while 12% showed radiological progression. With a median follow-up duration of 47 months, 5-yr OS was 94% and 5-yr DFS was 84%. 5 patients underwent re-surgery and 3 underwent reirradiation for recurrent disease. Late morbidities included stable cranial nerve palsies (29%), motor deficits (8%) and cataract (2.5%). Presently 148 (92.5%) patients are alive and free of disease on regular followup. Conclusion: Use of HT based IG-IMRT in benign and low grade tumours of brain and skull base is effective in achieving durable control with low acute and late morbidity in these long-term survivors.